Spontaneous external rupture of hydrocephalus in the occipital region in an infant: A rare case report - Ananta Rattan; Kamal Nain Rattan; Jasbir Singh; Poonam Dalal (Interdisciplinary Neurosurgery, 2019)
With the availability of advanced diagnostic and therapeutic modalities, late presentation of hydrocephalus is a very uncommon occurrence in the present era. Here, we report an 11-months infant with late presenting hydrocephalus with spontaneous rupture at the occipital region. Keywords: Hydrocephalus, Infant, Rupture, Occipital